2018
DOI: 10.3390/ijms19123878
|View full text |Cite|
|
Sign up to set email alerts
|

Annexin A1 May Induce Pancreatic Cancer Progression as a Key Player of Extracellular Vesicles Effects as Evidenced in the In Vitro MIA PaCa-2 Model System

Abstract: Pancreatic Cancer (PC) is one of the most aggressive malignancies worldwide. As annexin A1 (ANXA1) is implicated in the establishment of tumour metastasis, the role of the protein in PC progression as a component of extracellular vesicles (EVs) has been investigated. EVs were isolated from wild type (WT) and ANXA1 knock-out (KO) PC cells and then characterised by multiple approaches including Western blotting, Field Emission-Scanning Electron Microscopy, and Dynamic Light Scattering. The effects of ANXA1 on tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
65
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(72 citation statements)
references
References 50 publications
4
65
0
Order By: Relevance
“…A recent finding indicated that ANXA1 can be incorporated into EVs. The ANXA1-containing EVs leads to an activation of the EMT process, along with the increased motility of exosome-receiving PCCs [43] (Figure 1 and Table 1). However, another study indicated the opposing role of ANXA1 in PCCs.…”
Section: Anxa1mentioning
confidence: 97%
See 2 more Smart Citations
“…A recent finding indicated that ANXA1 can be incorporated into EVs. The ANXA1-containing EVs leads to an activation of the EMT process, along with the increased motility of exosome-receiving PCCs [43] (Figure 1 and Table 1). However, another study indicated the opposing role of ANXA1 in PCCs.…”
Section: Anxa1mentioning
confidence: 97%
“…As stated in Section 2.2.2, ANXA1 can be incorporated in PCC-derived EVs and modulate the motility of cancer cells. Beyond this, it was unequivocally addressed that ANXA1 in PCC-derived EVs can activate ECs, and it was ascertained by monitoring proliferation, migration, invasion and tube formation of endothelial cells [43] (Figure 2 and Table 2).…”
Section: Anxa1mentioning
confidence: 99%
See 1 more Smart Citation
“…The involvement of cancer-derived exosomes in EndMT remains unclear; however, relevant data are gradually accumulating, shedding light on this mechanism. For instance, it has been reported that exosomal Annexin A1 and RAC1/PAK2 induce EndEMT, whereas miRNA-200 suppresses EndEMT [85,112,113].…”
Section: Roles Of Evs In Endothelial-to-mesenchymal Transitionmentioning
confidence: 99%
“…A 24-well plate was coated with Matrigel (Becton Dickinson Labware, Franklin Lakes, NJ, USA) mixed to EGM-2 1:1 on ice and incubated at 37 ā€¢ C for 30 min to allow gelation to occur, as reported in Pessolano et al, 2018 [28]. HUVEC cells were added to the top of the gel at a density of 2 Ɨ 10 4 cells/well in the presence or not of sodium MSG and PCL-derived MSG.…”
Section: Tube Formation Assaymentioning
confidence: 99%